Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 211114553 species occurrences available in GBIF matching the query: { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Fossil", "BasisOfRecord is Living Specimen", "BasisOfRecord is Unknown evidence" ] } The dataset includes 211114553 records from 23049 constituent datasets: 1140 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 26568 records from LiquenCAT: Banco de datos de los líquenes de Cataluña. 5 records from Oosagitta gen. nov. from tropical Africa, with revision of two species and description of four new species (Coleoptera: Chrysomelidae, Galerucinae). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 156 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae). 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 5 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 27 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 342 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 5 records from A new species of Astyanax Baird & Girard (Characiformes: Characidae) from the upper rio Araguaia, Central Brazil. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 21 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 3035 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 878 records from COA Bird Collection (Arctos). 77 records from (Table 2) Distribution of calcareous benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 479 records from CBS Bacteria Database. 6 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 154 records from Sorensen distance for herbivores. 214 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 88 records from Total foraminifera counts of multinet M33/1_MSN1029. 118 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 36 records from Planktic foraminifera counts of sediment core V28-122. 20 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 1860 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 1 records from A new species of the mesopelagic isopod genus Xenuraega Tattersall, 1909 (Crustacea: Isopoda: Aegidae) from Japan, the second species in the genus. 125 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 5 records from Description of a new subspecies of Talicada nyseus (Guérin-Méneville, 1843) from Hainan, China (Lepidoptera: Lycaenidae), with notes on the genus Talicada Moore, 1881. 391 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 23 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 3986 records from FBIP: What are the impacts of global climate change on arid soil microbial communities?. 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 66 records from Trogonoptera brookiana mollumar d’Abrera, Doggett & Parker, 1976 (Lepidoptera: Papilionidae), a subspecies or a synonym?. 3247 records from Museu de Ciències Naturals de Barcelona: BGJBB. 570 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 3 records from Three new species of the barracudina genus Lestidium (Aulopiformes: Paralepididae) from the Indo-West Pacific. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 85 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 102 records from Nannofossil abundance of Hole 24-232. 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 31 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 1 records from Ueber eine noch nicht beschriebene Nothrus-Art. 2 records from First record of Orthelimaea himalayana (Ingrisch, 1990) (Orthoptera: Tettigoniidae: Phaneropterinae: Elimaeini) from India with description of its female. 4 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 2904 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 39 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 5 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 2 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 8 records from New cave-dwelling Plakina (Plakinidae, Homoscleromorpha, Porifera) from Martinique Island (French Antilles). 1305 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 1 records from A new aberrant Doryctinae genus (Hymenoptera: Braconidae) from French Guiana. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 318235 records from CAS Herpetology (HERP). 92 records from Review of Thoreyella Spinola with the description of two new species from Brazil (Heteroptera, Pentatomidae). 43804 records from Butler University Friesner Herbarium (BUT). 307107 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 5514 records from MCP-Aves - Coleção de Aves. 80 records from (Table 2g) Nannofossil distribution chart of petroleum well Swan-3. 46 records from Distribution of species of planktic foraminifera in bottom sediments from Core AK32-3336. 3 records from Hidden diversity in European bees: Andrenaamieti sp. n., a new Alpine bee species related to Andrenabicolor (Fabricius, 1775) (Hymenoptera, Apoidea, Andrenidae). 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 135 records from Nannofossil abundance of Hole 36-329. 29 records from The genus Chalybion Dahlbom, 1843 (Hymenoptera: Sphecidae) from Northwest Vietnam, with description of a new species. 4 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 12557 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 147 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 7 records from First records of Glaresidae (Coleoptera) in China, with the description of a new species from Inner Mongolia and Shaanxi. 100 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 20 records from Two Hexapleomera species from Japan, with a new species description and discussion of phylogenetic relationships within Hexapleomera (Crustacea: Tanaidacea). 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 23 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes (Reptiles). 26 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 2 records from Carnivores of Syria. 956 records from Vertebrados terrestres de San Juan de Camarones, Durango. 142 records from Botanical collection of the National Museum. 11622 records from French Grapevine Genetic Resources Center. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 7 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 3 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 24 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 31 records from Nannofossil abundance of Hole 6-53. 1 records from Arcanumophis, a new genus and generic allocation for Erythrolamprus problematicus (Myers 1986), Xenodontinae (Colubridae) from the Cordillera de Carabaya, southern Peru. 251 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 14 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 988 records from flower availability 2008 Alb-korrigiert. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 4 records from Dinoflagellate abundance of Hole 14-144. 43 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 282 records from Middlebury College Bee Collection. 1 records from A new species of Cyphocarididae (Crustacea, Amphipoda, Lysianassoidea) from off the northeastern Brazilian coast. 8 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 5 records from A new sponge species of the genus Antho (Demospongiae, Microcionidae) from the Tyrrhenian deep Sea. 28461 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 550 records from Pollen and spore abundance of Hole 42-380A. 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 3 records from Two new Brazilian species of Neapion Alonso-Zarazaga, 1990 subgenus Neotropion Alonso-Zarazaga, 1990 with a key to South American species (Brentidae: Apioninae). 1 records from The tadpoles of Murree Hills Frog Nanorana vicina (Anura: Dicroglossidae). 4 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 80 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 96 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 10 records from Analyses of the recent components of sediment core PS1277-1. 237 records from Nannofossil abundance of Hole 60-458. 1 records from A new species of Centrouropoda (Acari: Uropodidae: Uropodina), with a key to the world species of the genus. 48 records from A new species of Psilorhynchus (Teleostei: Psilorhynchidae) from the Ataran River Basin, Myanmar, with comments on the generic name Psilorhynchoides.. 1 records from Redescription of the remarkable Zhiltzovaia amabilis (Jewett, 1958) comb. nov. (Plecoptera, Perlodidae) based on types and new material from Himalaya and Pamir Mountain systems. 13736 records from MfN - Mallophaga Collection. 11961 records from MEXU/Leguminosae. 18 records from A new genus for the freshwater crab Potamonemus asylos Cumberlidgeı 1993 ı (Brachyura: Potamoidea: Potamonautidae) from Cameroonı Central Africaı with a key to the genera of the Potamonautinae. 5 records from Nannofossil abundance of Hole 6-53A. 2 records from Synchrotron micro-CT scanning leads to the discovery of a new genus of morphologically conserved echinoid (Echinodermata: Cassiduloida). 69 records from The coastal rove beetles (Coleoptera, Staphylinidae) of Atlantic Canada: a survey and new records. 12 records from Nannofossil abundance of Hole 29-283A. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 2 records from Waldstück Bremerhagen LK Bio Kl. 12. 18 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 5262 records from Spider Mites Collection of Jean Gutierrez. 1145 records from Planktic foraminifera counts of sediment core RC08-49. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 13 records from Ichneumonid wasps from Madagascar. VI. The genus Pristomerus (Hymenoptera: Ichneumonidae: Cremastinae). 1 records from A new name for Dendronephthya kukenthali Gravier, 1908 (Octocorallia, Nephtheidae): Dendronephthya perezi nom. n.. 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 15 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 505 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 609 records from Collection botanique Mulon L. (BOUM). 115 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 5 records from Garra roseae, a new species from the Makran region in southern Iran (Teleostei: Cyprinidae). 439 records from Implementación de la bioindicación en el Río Magdalena. 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 551 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 362 records from The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia. 52873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1 records from A short taxonomic note on the katydids from the genus Cercoteratura Gorochov, 2019 (Orthoptera: Tettigoniidae: Meconematinae), with a key to species. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 718 records from Inventario florístico de las Cactáceas del estado de Tamaulipas, México. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 13 records from Coccolith counts of multinet M32/5_MSN988. 293389 records from R. L. McGregor Herbarium Vascular Plants Collection. 49 records from The genus Litophyton Forskål, 1775 (Octocorallia: Alcyonacea: Nephtheidae) from Australia. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 4 records from Taxonomic revision of the Neotropical genus Ectophasiopsis Townsend, 1915 (Diptera: Tachinidae: Phasiinae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 204 records from Planktic foraminifera abundance of Hole 29-284A. 78 records from Planktic foraminifera abundance of Hole 49-409. 607514 records from Plant. 31 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 249 records from Calcareous dinoflagellates nominated in grain fraction > 20 µm. 207 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 2261 records from Records of the Wine Microorganism Culture Collection. 50 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 122 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 21 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 128 records from Pollen profile 2 from Richland Creek. 24 records from Chapter 7: Linnaean Plant Names and their Types (part Q). 5168 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 34 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 13162 records from Observations du Conservatoire botanique national du Bassin parisien.. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 12859 records from Colecção Entomológica IIA. 4 records from Rediscovery of Lustrina Kurian (Hymenoptera, Chrysididae), with redescription of L. assamensis Kurian. 17155 records from MZFC/Coleccion de Aves. 2530 records from Fossil Birds. 114567 records from TNHC Herpetology Collection. 272 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 1292 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 143 records from Foraminifera abundance of Hole 48-406. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 89 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 110 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel (Plantas). 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 4681 records from Museu Darder de Banyoles. 521 records from Benthic foraminifera abundance of Hole 82-558. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 11 records from More new Diplotrema earthworm species from southern Mexico (Annelida, Crassiclitellata, Acanthodrilidae, Acanthodrilinae). 316 records from Moss species from Heard Island, 1987 and 2000. 43 records from Nannofossil abundance of Hole 10-91. 940 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 7148 records from DMNS Egg Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 1340 records from Geochemistry and sedimentology on core POS200/10_6-2. 146 records from Colección de moldes endocraneanos del CENPAT. 1095 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 20 records from Biting midges of the tribe Ceratopogonini (Diptera: Ceratopogonidae) from the Middle East, with keys and descriptions of new species. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 4 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 33 records from Nannofossil abundance of Hole 5-33. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 3975 records from Study on plankton at the port of Ostend in 1965. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5 records from Ostracods (Crustacea) associated with microbialites across the Permian-Triassic boundary in Dajiang (Guizhou Province, South China). 7 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 1 records from Hornmilben (Oribatida) [pages 261 to 322]. 20 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 2 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1990 records from Orthoptera - SMF. 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2 records from Re-evaluation of the morphology of the monotypic genera Lycastonereis Rao, 1981 and Ganganereis Misra, 1999 (Annelida, Phyllodocida, Nereididae). 1121 records from Collection Meebold HBG Herbarium. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 239 records from Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution. 7 records from Cyphocharax boiadeiro, a new species from the upper rio Araguaia, Amazon basin, Brazil (Characiformes: Curimatidae). 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from First fossil Eccoptarthridae (Coleoptera: Curculionoidea) from the Mesozoic of China. 17 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15 records from Review of the genus Pagastia Oliver (Diptera: Chironomidae: Diamesinae) from North America, with description of P. (P.) subletteorum sp. nov.. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 101 records from Planktic foraminifera abundance of Hole 2-12C. 1702 records from BioGIS - Bryophytes - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 3 records from First description of the male of the easternmost Harpactea species, H. parthica (Araneae: Dysderidae). 50419 records from University of Michigan Museum of Paleontology - Vertebrates. 32602 records from The Brown University Foraminiferal Data Base (BFD). 457 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 3280 records from (Table 7) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-873B. 42 records from Morphological and molecular analyses support the amphi-Atlantic distribution and taxonomic status of the snapping shrimp Alpheus intrinsecus Spence Bate, 1888 (Crustacea: Decapoda: Alpheidae). 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 54918 records from Herbarium Universitatis Daugavpiliensis. 5 records from Some Cheilostomata (Bryozoa) from the Java Sea, central Indonesian Archipelago with a description of Pleurocodonellina jeparaensis n. sp. (Smittinidae). 33361 records from SANT-Algae. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 871 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 9 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 1151 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 29 records from Systematics, ecology and distribution of the mygalomorph spider genus Cteniza Latreille, 1829 (Araneae, Mygalomorphae, Ctenizidae). 352 records from Universidad del Valle de Guatemala - Colección de Artrópodos. 7 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 85 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 2 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 335 records from Dinoflagellate cyst counts on sediment core ABC26. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 48 records from Swedish Malaise Trap Project (SMTP) - small parasitic aculeate families. 4 records from Lectotype designation and distribution updates on the freshwater shrimp species Atyaephyra stankoi Karaman 1972. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 106 records from Abundance of radiolaria at station UT99-5-1. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 76537 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 23 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 20084 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 307397 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7804 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT (Plantas). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 167 records from Total foraminifera counts of multinet M21/6_MSN787. 231 records from Range table from benthic foraminifers in ODP Hole 161-974B. 1 records from Stylogomphus thongphaphumensis (Odonata: Anisoptera: Gomphidae), a new gomphid dragonfly and the first record of S. malayanus Sasamoto, 2001 from Thailand. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 11586 records from (Table 1) Range table of planktonic foraminifers from ODP Hole 166-1006A sediments. 3 records from New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA. 173 records from UWIZM Anoles. 218 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 11 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 11 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1017 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 11 records from Ektomykorrhizen auf VIP Alb (Wald). 25 records from Novas Espécies De Acrosternum Subgênero Chinavia (Heteroptera, Pentatomidae, Pentatomini). 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 34 records from The Moroccan species of Chyromyidae (Diptera) with descriptions of five new species of Aphaniosoma Becker. 8 records from Benthic macrofauna abundance of sediment core 12930-063. 184 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 74123 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 399 records from Pollen analysis of sediment profile TR0 from Truennensee. 526 records from FernsDarwinCore. 3 records from Überall ist Wunderland. 2451 records from Macrobenthos Chukchi Sea, 1986. 4269 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 222 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 10 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 5 records from Note on the genus Lecanophryella (Ciliophora: Suctorea) with description of a new species from west coast of India. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 124 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 1 records from Taxonomy of the weevil genus Plumolepilius Barrios-Izás & Anderson (Coleoptera Curculionidae: Molytinae: Conotrachelini): new species from Central America. 22 records from Microzooplankton abundance and biomass at station TT043_13-1. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 24 records from A Gondwanan concept of Simplimorpha Scoble (sensu lato): a step toward clarity in the generic diagnostics of global Nepticulidae (Lepidoptera). 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 5 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 19 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 449 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 1647 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 167 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 109 records from Faunal assemblage of sediment core TR149-31. 1543 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 43 records from Nannofossil abundance of Hole 49-409. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 134 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 73 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 29 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 14 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 2 records from Two new species of Amphinemura (Plecoptera: Nemouridae) from Tibet. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 4670 records from Weber State University Herbarium. 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 5 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 639 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 87 records from Diatom abundance of Hole 95-613. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 22 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 4 records from Haematophagous biting midges of the extant genus Culicoides Latreille (Diptera: Ceratopogonidae) evolved during the mid-Cretaceous. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 6 records from Nueva especie de Aleuropleurocelus Drews y Sampson (Hemiptera: Aleyrodidae) y clave para especies del grupo de forma oval. 1957 records from SIM-Fungal records compiled by Joan Montón. 783924 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 1 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 798 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 13 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1513 records from M. Gollop Collection. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53261 records from Naturalis Biodiversity Center (NL) - Diptera. 2 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 2 records from Schulhof Gymnasium Hürth Bonnstrasse. 200 records from Chapter 7: Linnaean Plant Names and their Types (part O). 1 records from Berlese's Primitive Oribatid Mites. 18 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 453 records from Benthic foraminifera counts of sediment core PS1852-2. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2497 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 7 records from Taphonomy and environment of deposition of a juvenile tyrannosaurid skeleton from the Hell Creek Formation (latest Maastridhtian) of southeastern Montana. 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 110 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 225073 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 224 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 19 records from Heinersdorfer Sumpfwiese. 291402 records from ARABEL - Arachnologia Belgica. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3257 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 348 records from Antarctic pycnogonids. 552 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 62799 records from MLZ Bird Collection (Arctos). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 1 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 15 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 3 records from Wiese am Waldrand (Gurtweil). 4976 records from Gastropod Specimens of the Yamagata Prefectural Museum. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 385 records from UWYMV Herpetology Collection (Arctos). 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 5 records from A remarkable new species of Micropeza Meigen (Diptera: Micropezidae) from Caatinga biome, Brazil. 108523 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 209 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2257 records from Plant specimens of Bihoro Museum. 96 records from Planktic foraminifera counts at CTD station PS55/063. 232 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 174 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 9 records from First record of the genus Agnara (Isopoda: Oniscidea) from Iran with descriptions of two new species. 25 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 11 records from The InBIO Barcoding Initiative Database: Portuguese Stag beetles (Coleoptera, Lucanidae). 79 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1 records from Xibalbanus cozumelensis, a new species of Remipedia (Crustacea) from Cozumel, Mexico, and a molecular phylogeny of Xibalbanus on the Yucatán Peninsula. 394 records from Reptilia ZMK. 880 records from Diversity of Spiders from Azorean Trails. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 2012 records from Pollen profile RAC20, Lake Racou, France. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 463 records from Foraminifera abundance of sediment core IN68-9. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 7873 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 19740 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 60 records from Key to South American genera of Acanthocinini (Coleoptera, Cerambycidae Lamiinae) with erect setae on elytral surface. 205 records from Japan Collection of Microorganisms(Basidio). 6237 records from Plecoptera. 22 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 5 records from Amphibia, Bokermannohyla nanuzae, Scinax curicica, Leptodactylus camaquara, Physalaemus evangelistai, and Proceratophrys cururu: Distribution extensions. 3 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 3 records from Revision of the genus Exsuperantia Özdikmen, 2009 (Tetractinellida: Phymaraphiniidae) with description of a new species from the Atlantic Ocean. 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 1 records from Flora. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 58 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 103 records from Foraminifera species abundances from tow TT011_5-MOC63. 8 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 14 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 24 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 8 records from Reconsideration of the apterous carventine genus Crassocoris and description of Paracrassocoris gen. nov. from China (Hemiptera: Heteroptera: Aradidae). 34 records from NZCS Brownsberg Nature Park Monitoring. 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 3652 records from La flora útil de dos comunidades indígenas del Valle de Tehuacán-Cuicatlán: Coxcatlán y Zapotitlán de las Salinas, Puebla. 14 records from Collection Amphibia fossil SMF. 62913 records from Collection Mollusca SMF. 10 records from Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae). 164 records from Total foraminifera counts of multinet M6/7_MSN100. 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 222 records from Neogene palynomorpha from site 81-552. 92 records from Protozoa Abundance_Microbial Parameters. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 192 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1952 records from ISM Ichthyology Collection. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 1889 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 27 records from Nannofossil abundance of Hole 9-79. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 143094 records from The Himalayan Uplands Plant database (HUP Version 1). 1 records from Artenvielfalt auf dem Schulgelände. 8425 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 23 records from A key to the species of Protogamasellus (Acari: Ascidae), with a new species from the Brazilian Pantanal. 12654 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 26 records from Results of a recent bat survey in Upper Myanmar including new records from the Kachin forests. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 27 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 142 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 57 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 7 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 6 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (PLECHA). 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 29941 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 116 records from Dinoflagellate cysts of ODP Hole 189-1172D. 631 records from Planktic foraminifera abundance of Hole 45-395. 68746 records from Entomology Collection at the Natural History Museum of Utah. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 4 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 120231 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 3184 records from Herbarium specimens of Limoges university (LIMO). 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 128557 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13662 records from UTEP Invertebrates (Arctos). 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 998 records from Korean Ethnobotany Database. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 1333 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 4 records from Planktic foraminifera abundance of Hole 19-191A. 23643 records from CNIN/Abejas de México/Apoidea. 1248 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1564 records from Flora útil del Municipio de la Huerta, Jalisco. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 1719 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 5 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 151 records from Total foraminifera counts of multinet M36/6_MSN1196. 30 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 15 records from Nannofossil abundance of Hole 10-93. 317 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 18 records from Six new species of the genus Nazeris (Coleoptera, Staphylinidae, Paederinae) from China. 9 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 294 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 275 records from Planktic foraminifera counts of sediment core V14-77. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 302 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 276503 records from hymenoptera. 116936 records from Naturalis Biodiversity Center (NL) - Crustacea. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 70 records from The genus Hoplothrips in Australia (Thysanoptera, Phlaeothripinae), with eleven new species. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 8555 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 3544 records from The Broward College Insect Collection. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 25987 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 409 records from Distribution of nanoplankton at trap WR2. 1191 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 54 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 2 records from Naturgrundstück (Eutin). 12127 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 28 records from Korean Plant Virus Database. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 49 records from Herbarium Senckenbergianum (FR) - Protista. 250 records from Colección de helechos de la FML. 3 records from Zoology in the Middle East. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 24 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 4447 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 150 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 36 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 5915 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 1 records from Patterns of head shape and scutellation in Drymarchon couperi (Squamata: Colubridae) reveal a single species. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 61 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 17 records from Analyses of the recent components of sediment core PS1011-1. 300440 records from Allan Herbarium (CHR). 257400 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 69 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1480 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 208 records from Chapter 7: Linnaean Plant Names and their Types (part V). 3 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 306 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 8 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 6 records from Foraminifera abundance of Hole 58-442. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 13 records from Coleção de Coleoptera da Universidade de Brasília. 396 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2 records from Warnowtal (Rostock). 855 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 31 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 28108 records from Marie-Victorin Herbarium (MT) - Bryophytes. 433 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 109 records from Dinoflagellate cysts from sediment core PS1295-4. 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1071 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 10 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 183 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 18 records from Exotic speciments butterflies at Museum Zoologi Bogor, Indonesia. 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 3215 records from Utah State University, Intermountain Herbarium. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 830 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 886 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 9902 records from DSMZ Bacteria. 276284 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 97241 records from Naturalis Biodiversity Center (NL) - Pisces. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 477 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 387 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 495 records from Radiolaria assemblage in sediment core GIK23414-6. 25 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 386 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 320 records from Myxomycetes collection of the University of Eastern Finland. 20 records from New data on the fauna of China, part I: the taxonomy of the millipede family Julidae (Diplopoda). 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 35 records from Planktic foraminifera abundance of Hole 84-566C. 17 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 25 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 2 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 53 records from Nannofossil abundance of Hole 1-3. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 110 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 71 records from Nannofossil abundance of Hole 6-55. 126 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 1798 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 751 records from Planktic foraminifera abundance of Hole 27-262. 126934 records from Arizona State University Hasbrouck Insect Collection. 35 records from Planktic foraminifera abundance of Hole 27-260. 351 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 194 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 2 records from Amtsrain Apolda-Zottelstedt. 72 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 6 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 55 records from Temporary expansion to shelf depths rather than an onshore-offshore trend: the shallow-water rise and demise of the modern deep-sea brittle star family Ophiacanthidae (Echinodermata: Ophiuroidea). 1 records from Norwegian Lepidoptera working group. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 1 records from Sarcocheilichthys vittatus, a new species of gudgeon (Teleostei: Cyprinidae) from the Poyang Lake Basin in Jiangxi Province, South China. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 3 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 600 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 11 records from On the Bennelongia nimala and B. triangulata lineages (Crustacea, Ostracoda) in Western Australia, with the description of six new species. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 995 records from Pollen profile ADR353. 101 records from Foraminifera species abundances from tow TT011_7-MOC66. 270 records from bmhs_weatherheadshell_collection. 1 records from Sächsische Schweiz (Pfaffenstein). 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 755 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 899 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 10898 records from Inventario de Hymenóptera; parasítica en México. 374 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 12888 records from MfN - Fossil Fish Collection. 4 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 65 records from Planktic foraminifera abundance of Hole 9-76. 3741 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 182 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 2 records from AKG-Gelände (Bensheim). 237 records from Planktic foraminifera abundance of Hole 21-207. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 15 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 23 records from Benthic foraminifera abundance of Hole 93-603. 3 records from Cyana barbora, a new species from Sichuan, southwestern China (Lepidoptera Erebidae, Arctiinae, Lithosiini). 11802 records from WOLL AVH data. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 6 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3638 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 20941 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 39 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1 records from Descriptions of new Genera and Species of Odonata in the Collection of the British Museum, chiefly from Africa.. 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 731 records from Planktic foraminifera counts of sediment core V27-178. 1 records from Lebensraum Gesamtschule (Langerwehe). 314 records from Foraminifera abundance of Hole 64-481. 6 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 5 records from Discovery of the genus Micropeneta Pic in China, with description of a new species (Coleoptera: Tenebrionidae: Gnathidiini). 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 310 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 15621 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 8 records from Revision of the Western Palae arctic species of the genus Casinaria H (Hymenoptera, Ichneumonidae, Campopleginae). 6 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 123 records from Total foraminifera counts of multinet M21/2_MSN648. 1350 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 2197 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 6 records from A revision of the genus Zyras (Zyras) Stephens, 1835 (Coleoptera, Staphylinidae, Aleocharinae). I. Current classification status and the redefinition of the genus. 272 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 954 records from NW Pacific Deep-sea Benthos Biodiversity (Beneficial Project). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 211 records from Planktic foraminifera abundance of Hole 14-142. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 2 records from A New Genus And Species Of Panaphantina (Coleoptera: Staphylinidae: Pselaphinae: Euplectitae: Trichonychini) From Australia. 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 4 records from Two new species of heavily calcified cyclostome bryozoans from the intertidal of Akkeshi Bay, Hokkaido, Japan. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 59 records from Nannofossil abundance of Hole 73-521A. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 685 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 1723 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 1 records from Acantorna-a new genus of Hymedesmiidae (Porifera, Demospongiae Poecilosclerida) from the western Aleutian Islands of Alaska with description of Acantorna tahoma n. sp.. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 9489 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 488 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5316 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 36 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 60 records from Total foraminifera counts from M35/1_MSN1065. 196 records from Foraminifera abundance of Hole 33-317A. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 6 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 14 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 125 records from Total foraminifera counts of multinet M21/2_MSN650. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 10 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 1298 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 98 records from Nannofossil abundance of Hole 67-499B. 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 10 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 2 records from Gladiopycnodontidae, a new family of pycnodontiform fishes from the Late Cretaceous of Lebanon, with the description of three genera. 83 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 2 records from Two new pill millipedes (Diplopoda: Glomerida: Glomeridae) from high mountains of Vietnam. 66116 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 9 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 5 records from Four new Oriental species of the ‘ Cephennomicrus group’ (Coleoptera: Staphylinidae: Scydmaeninae). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 79 records from Nannofossil abundance of Hole 31-299. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 1 records from West Palaearctic species of the genus Diostracus Loew, 1861 (Diptera: Dolichopodidae). 9373 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 2 records from Dorfrand Mauderode. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 9 records from Nannofossil abundance of Hole 2-11. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18224 records from K-State Museum of Entomological and Prairie Arthropod Research. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 172 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 238 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2371 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 191 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 15 records from Nannofossil abundance of Hole 6-48B. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 214 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 29876 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 81 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 13 records from A new species of Pimelodella Eigenmann & Eigenmann, 1888 (Siluriformes: Heptapteridae) from the Orinoco River basin. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 104 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 24795 records from Université d'Aix-Marseille. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 4 records from MfN - Micropaleontology. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 79 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 12 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 912 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 66 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 40 records from Planktic foraminifera abundance of Hole 14-137. 2545 records from UWYMV Bird Collection (Arctos). 11994 records from Hatikka Observation Database. 57 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 1 records from A new Atheta species from the West Caucasus and a redescription of A. brevapicalis (Coleoptera: Staphylinidae: Aleocharinae). 1 records from Synopsis of the extinct Batrachia, Reptilia and Aves of North America. 200187 records from inatura - Erlebnis Naturschau Dornbirn. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 168 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 2 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 302 records from New data on species diversity of Annelida (Oligochaeta, Hirudinea) in the Kharbey lakes system, Bolshezemelskaya tundra (Russia). 130 records from Total foraminifera counts of multinet M21/6_MSN784. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5779 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 50 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 5 records from Parochodaeus bituberculatus (Erichson) (Coleoptera: Ochodaeidae) and Faargia gentilii (Martínez) (Coleoptera: Scarabaeidae), two species newly discovered in Chile. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 107580 records from Database of invertebrates collected in Mongolia. 1 records from A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 917 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 38 records from Nannofossil abundance of Hole 10-89. 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 6 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 605 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 190 records from Pollen record of profile 3TZ. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 396164 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 31 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 3 records from Coccolith counts of multinet M32/5_MSN981. 100 records from Brock University Herbarium (BU). 20 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 148 records from Herbarium BSG Hepaticopsida. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 1 records from Diverse mechanisms of feeding and movement in Cyclorrhaphan larvae (Diptera). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 123 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 3004 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 32 records from Total foraminifera counts of multinet FCA97C_MSN1345. 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 3712 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 817 records from Lucanidae. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 516 records from Planktic foraminifera counts of sediment core A15-558. 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 3 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 185 records from Size of planktic foraminifera at CTD station PS55/051. 26841 records from MSUM Ichthyology and Herpetology Collections. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 1 records from Juvenile eucladid crinoid from the Middle Devonian of Turkey. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 407 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 16809 records from Genebank, National Institute of Agrobiological Sciences. 12 records from The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 7600 records from ERBG AVH data. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 64 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 184807 records from Tiroler Landesmuseum Ferdinandeum. 14 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 32 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1227 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 78 records from Mammals (GNHM-MM). 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 2 records from The first Cacomorphocerus species (Coleoptera, Cantharidae) from Rovno amber a second species of the genus with 11 - segmented antennae. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 132 records from Abundance of radiolaria at station UT99-23-2. 27 records from Planktic foraminifera abundance of Hole 51-417B. 375 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 2826 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 22 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from Tibetyrus gen. nov., a new myrmecophilous Tyrini from Xizang, China (Coleoptera: Staphylinidae: Pselaphinae). 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 8 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 3 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 911 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Ostracoda abundance of Hole 24-238. 18 records from Thirteen new records of ferns from Brazil. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 660 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202628 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 4782 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 3 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 36 records from Review of the millipede family Haplodesmidae Cook, 1895, with descriptions of some new or poorly-known species (Diplopoda, Polydesmida). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 8 records from A new species of Paralithoxus (Siluriformes: Loricariidae: Ancistrini) from the highlands of Serra da Mocidade, Roraima State, Brazilian Amazon. 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 697 records from 2019_NSMK_PL. 540 records from Foraminifera abundance of Hole 74-526A. 184 records from Dinoflagellate abundance of Hole 81-555. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 1872 records from Herbier National de Guinée (HNG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 404 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 300 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 49 records from Nannofossil abundance of Hole 27-259. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 77 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3363 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 57 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 177 records from Chironomid remains in the sediment sequence of Site PG1212. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3404 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 46 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 86 records from UWIZM Cnidarians. 20 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 356 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 1059 records from irregularia_mexico. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 22062 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 177938 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40339 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 41 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1 records from Genetic and morphological evidence for cryptic species in Macrobrachium australe and resurrection of M. ustulatum (Crustacea, Palaemonidae). 2 records from Benthic foraminifera abundance of Hole 42-376. 1234 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 876 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2899 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 2741 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Tromsø. 48 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 2 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 134 records from Faunal assemblage of sediment core TR149-32. 1 records from A complementary description of the male of Kyphopteryx yangi (Plecoptera: Taeniopterygidae) from China. 516 records from Nannofossil abundance of Hole 15-149. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 41 records from Registros Primates Neotropicales Convocatoria APC. 54 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 118 records from Pollen record of profile 3TZ2. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna” (Reptiles y anfibios). 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 1 records from Memecylon pseudomegacarpum M. Hughes (Melastomataceae), a new species of tree from Peninsular Malaysia. 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 38 records from Revision of the stygobiont gastropod genera Plagigeyeria Tomlin, 1930 and Travunijana Grego & Glöer, 2019 (Mollusca; Gastropoda; Moitessieriidae and Hydrobiidae) in Hercegovina and adjacent regions. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7010 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 11 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 311 records from Benthic foraminifera abundance of Hole 41-366A. 52 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 2 records from A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera Reduviidae) from Vietnam. 1 records from Redescription of Favognathus insularis (Luxton) (Acari: Trombidiformes: Cryptognathidae) from Brazil, with a key to the world species of Favognathus. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 2128 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 23 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 43 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 1000 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 128 records from Total foraminifera counts of multinet POS247/2_MSN1386. 8 records from Taxonomy and diversity of coelobite bryozoans from drift coral cobbles on Co To Island, northern Vietnam. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 49 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 561 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 813 records from Microfossil abundance of Hole 16-158. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 342 records from Nannofossil abundance of Hole 78-543. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 23 records from Total foraminifera counts of multinet FCA97C_MSN1339. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 82 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 361 records from Nannofossil abundance of Hole 66-490. 4400 records from USAC Mammals Collection. 193 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 3 records from A new mayfly species of Rhoenanthus (Ephemeroptera: Potamanthidae) from Peninsular India. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 449 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 4000 records from Fossil Specimens of Komatsu City Museum. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 9 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 238 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 38 records from Planktic foraminifera counts of sediment core RC13-154. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 1402 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 13 records from Diatom abundance of Hole 60-460. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 194 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 569 records from (App 2) Relative contents of benthic foraminifera species in Holocene sediments from Core ASV11-858-3. 6 records from A new fossil species of Trentepohlia (Diptera, Limoniidae) from the Dominican Miocene. 15 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 4 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 53 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 30 records from Nannofossil abundance of Hole 24-233A. 128 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 56 records from A taxonomic revision of the Western Palaearctic genus Cacochroa Heinemann 1870 (Lepidoptera, Depressariidae, Cryptolechiinae) with description of a new genus and a new species. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 78 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 18 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 384 records from Nannofossil abundance of Hole 17-167. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009 (Región golfo centro). 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 292 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 289 records from bmhs_butterfly_collection. 2646 records from Distribution of major planktic foraminifer at Site 177-1090. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 702 records from Planktic foraminifera counts of sediment core V04-8. 102 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 172 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 10 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4212 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 7883 records from MfN - Fossil plants (Paleophytic). 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 62628 records from EAC - Herbário Prisco Bezerra. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1136 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 18 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 3 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 1564 records from Leif Richardson Vermont Bee Specimens. 247 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 153 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 29618 records from Collection Crustacea - ZMB. 1 records from A gall mite, Aceria rhodiolae (Acari: Eriophyidae), altering the phytochemistry of a medicinal plant, Rhodiola rosea (Crassulaceae), in the Canadian Arctic. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 1201 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 66 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 14 records from Nannofossil abundance of Hole 25-249. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 50 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1386 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 154 records from Dermaptera in the icipe collection. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2336 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 65 records from Three new species and new records of cuckoo bees of the genus Epeolus in Turkey (Hymenoptera: Apidae: Nomadinae). 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 171 records from Foraminifera abundance of Hole 57-440A. 51 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 1 records from New collections of freshwater crabs from northern Madagascar, with the description of a new species of Foza Reed & Cumberlidge, 2006 (Brachyura, Potamonautidae), and comments on their conservation status. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 8 records from Four new species of Rhyacophila Pictet 1834 (Trichoptera: Rhyacophilidae) from Southeast Asia. 1939 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 1098 records from What bug is that. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 97 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 1 records from Cretessenia roccamenaica nov. sp. (Acari: Prostigmata: Chyzeriidae: Chyzeriinae) from Sicily, Italy. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 102 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 9 records from Five new species of the genus Noeetomima Enderlein (Diptera: Lauxaniidae) from China, with a key to world species. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 153 records from Planktic foraminifera abundance of Hole 18-181. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 21 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 88 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1562 records from Colección del Herbario de la Universidad de los Llanos. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 42 records from Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak. 937 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 20 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 331 records from Pollen data of trap CB4. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 49 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 76 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 80 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 1 records from Notes on and key to the genus Phengaris (s. str.) (Lepidoptera, Lycaenidae) from mainland China with description of a new species. 1848 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 2 records from Microfossil abundance of Hole 21-208. 200 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 896 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 2 records from Myzostoma khanhkhoaensis (Myzostomida), a new myzostomid species from the Nhatrang Bay, Vietnam. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 94 records from The Dragon-flies (Odonata) of Palestine, based primarily on collection made by Dr. P. A. Buxton, with Notes on the Species of the Adjacent Regions.. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 5951 records from Collection Echinodermata SMF. 12 records from New species of the Neotropical genus Campatonema Jones (Geometridae, Ennominae) with the first description of the female. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 42702 records from MfN - Fossil vertebrates IV. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 4 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 687 records from Planktic foraminifera abundance of Hole 42-372. 65 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 49491 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 3439 records from MEXU/Flora de Oaxaca. 3 records from Two new species of freshwater crabs from the highlands of northern Uganda, East Africa and a redescription of Potamonautes amalerensis (Rathbun, 1935) stat. rev. from Mount Kadam (Brachyura: Potamoidea: Potamonautidae). 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 207 records from Nannofossil abundance of Hole 66-488. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 83 records from Heavy minerals of sediment core PL94-64. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1914 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 9 records from Notes on Oriental Clivinini and the description of two new species (Coleoptera: Carabidae: Clivinini). 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 39139 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 193 records from (Table 6) Ostracod assemblages of sediment core 9409. 4 records from Danielsberg (Mölltal, Kärnten). 8 records from Nannofossil abundance of Hole 39-353A. 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 232661 records from Oklahoma Vascular Plants Database Provider. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 3691 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 661 records from Targeting a portion of central European spider diversity for permanent preservation. 627 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 100 records from Nannofossil abundance of Hole 3-15. 6977 records from 2019_NSMK_PL_2. 589 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 391 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Description of Pseudosteineria longisetis sp. n. from northeastern Brazil with a review of the genus Pseudosteineria Wieser, 1956 (Nematoda: Xyalidae). 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 6 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 650 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 178 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 31199 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 4 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 8980 records from MEXU/Tipos de plantas vasculares. 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1584 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 3 records from The Genus Pseudopomyza (Diptera: Nerioidea) in Tasmania, with Description of a New Species. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 2 records from Landschaftspflegehof (Berlin). 4 records from One new species of the genus Xizicus Gorochov, 1993 (Orthoptera: Tettigoniidae Meconematinae) from Guangxi, China. 1 records from Bachpatenschaft Beeke. 51 records from Total foraminifera counts from M35/1_MSN1051. 14546 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 50 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 2 records from Artenvielfalt auf den Elbwiesen (Dessau). 19 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2950 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 681 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 12 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 78 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 2 records from A new species of Seira (Collembola: Entomobryidae) from northeastern Brazil. 17713 records from NCSM Mammals Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 1 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 101 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 96290 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 14 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 1 records from On the Chilopoda from Turkey. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 9 records from A contribution to taxonomy of the superfamily Grylloidea Laicharting from Yunnan, China (Orthoptera: Grylloidea). 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 18 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 2 records from Planktic foraminifera counts of multinet PS2616-5. 17 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 152 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 9 records from A new species of the genus Goera Stephens (Trichoptera, Goeridae) found in madicolous habitats in Amami-Oshima, southwestern Japan. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 3 records from Naturschutzgebiet Lochbusch-Königswiesen. 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 70 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 27 records from Review of Neocynorta Roewerı 1915 with two new generic synonymies (Opiliones: Gonyleptoidea: Cosmetidae). 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 7814 records from Odonata de Veracruz. 622 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 309 records from Chapter 7: Linnaean Plant Names and their Types (part T). 1447 records from Planktic foraminifera abundance of Hole 18-173. 712 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 83 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 3 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 15 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 5120 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 4 records from Tortonian teleost otoliths from northern Italy: taxonomic synthesis and stratigraphic significance. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 77 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 440 records from Wichita State University Collection. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 6859 records from Plan de vertebrados de la Patagonia. 10 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 18 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 4055 records from Distribution of planktic foraminifera of sediment core M35003-4. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 274 records from Planktic foraminifera abundance of Hole 22-217. 58 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 3 records from Chemistry supports the identification of gender-specific reproductive tissue in Tyrannosaurus rex. 5 records from A new species of Gamasellodes Athias-Henriot (Mesostigmata: Ascidae) from Brazil and a key to the world species of the genus. 14 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 647 records from pbzt_insect_biodiversity. 7 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 281 records from NZCS Upper Tapanahony Expedition 1991. 9 records from A new subspecies of Delias clathrata Rothschild, 1904 and records of other Delias species occurring on Mount Hagen, Papua New Guinea (Lepidoptera: Pieridae, Pierinae). 1 records from Oppia nitens. 24 records from Tanzanian Vertebrate Collection. 7 records from Three new species and one new record of Torrenticolidae (Acari, Hydrachnidia) from Wuyishan with an updated key for Chinese fauna. 42 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 804 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 5 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 603 records from Fossil (NSMK-FO). 2 records from First Jurassic grasshopper (Insecta, Caelifera) from China. 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 7 records from Philippogalla, a new genus for Philipposcopus modestus (Baker) from the Philippines, and a new species of Philipposcopus (Hemiptera: Cicadellidae: Idiocerinae) from China. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 16 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 10 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 6 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 128 records from Coleção de Nematoda do Museu Nacional - UFRJ. 8 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 6 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 3 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 69 records from Total foraminifera counts of multinet M21/5_MSN731. 9 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 22 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1741 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1123 records from Planktic foraminifera abundance of Hole 72-516F. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 4728 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 5 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 7 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 11249 records from Heteroptera collections of SW Finland. 361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 9 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 276 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 2740 records from Fungi specimens of Saitama Museum of Natural History. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 6 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 26 records from New acoustic and molecular data shed light on the poorly known Amazonian frog Adenomera simonstuarti (Leptodactylidae): implications for distribution and conservation. 31 records from Three new species of Diduga Moore, [1887] (Lepidoptera, Erebidae, Arctiinae) from Cambodia. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 5 records from Thalassironus filiformis sp. nov. (Nematoda, Enoplida) from the South China Sea. 761 records from Planktic foraminifera abundance of Hole 72-518. 1 records from Oribates fusifer. 24 records from Paracobitis abrishamchiani, a new crested loach from the southern Caspian Sea basin (Teleostei: Nemacheilidae). 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 4 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Ninia (Serpentes: Dipsadidae) from Chocó-Magdalena biogeographical province, western Colombia. 605 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 2 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 7 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 75 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 46682 records from Bosque Mesófilo de Montaña de México. 57 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 3 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 4 records from Rex, sit: digital modeling of Tyrannosaurus rex at rest. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 124473 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 477 records from Planktic foraminifera distribution of sediment core SU81-07. 5410 records from Collection ornithologique A. Maës. 30 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 2 records from New Entodiniomorphid Ciliates, Buetschlia minuta n. sp., B. cirrata n. sp., Charonina elephanti n. sp., from Asian Elephants of Turkey. 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 3 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 13 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 1490 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 11704 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 37 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 452759 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 3 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 7044 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 258 records from Malawi-Histeridae-Biodiversity-Data. 1286 records from Planktic foraminifera abundance of Hole 7-64. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 4439 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 25374 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 1173 records from Pollen profile from Seminary School Basin. 34 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 51 records from Benthic foraminifera and algae abundance of Hole 35-325. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 5139 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1933 records from Carabidae of the European North-East of Russia. 4046 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 44 records from Microzooplankton abundance and biomass at station TT045_15-2. 12 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 102476 records from Denver Museum of Nature & Science - Entomology. 242 records from FBIP: Identification of polychaetes used as bait. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 408 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 221 records from Revision of the genus Dziriblatta Chopard, 1936 (Blattodea, Ectobiidae, Ectobiinae) from North Africa, Spain, and the Macaronesian islands. I. The nine subgenera of the genus. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 62 records from Benthic foraminifera abundance of Hole 84-566C. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 660 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 454 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 8 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 10212 records from Spider (NSMK-SP). 30608 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 101 records from Mammals of Korea: a review of their taxonomy, distribution and conservation status. 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 10636 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 42 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 6 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 1 records from Nottekanal, Klasse 7 - 10. 77 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 574 records from Percentages of planktonic foraminifera species in sediment core V30-40. 245 records from Nannofossil abundance of Hole 37-333. 5923 records from Australian Coral Ecoregions. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 1 records from The fossil crown wasp Electrostephanus petiolatus Brues in Baltic Amber (Hymenoptera, Stephanidae): designation of a neotype, revised classification, and a key to amber Stephanidae. 477 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 8 records from Données taxonomiques et éthologiques nouvelles sur quatre espèces de Cigales du Sud thaïlandais (Rhynchota, Cicadoidea, Cicadidae). 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 2929 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 1874 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1313 records from Diatom assamblage in samples from sediment trap OG5. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 9 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4221 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 11 records from Late Cretaceous dinosaurs from the Denver Basin, Colorado. 897332 records from MICROBIS database. 9 records from The bark louse family Stenopsocidae (Psocodea: Psocomorpha) newly recorded from Laos, with description of three new species. 5 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 2 records from Holorchis castex n. sp. (Digenea: Lepocreadiidae) from the painted sweet-lips Diagramma pictum (Thunberg, 1792) (Perciformes: Haemulidae) from New Caledonia. 146 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 604 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5710 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 36 records from A new species of Heliogomphus from Vietnam (Odonata: Gomphidae). 37 records from Description of a new species of catshark, Atelomycterus marnkalha n. sp. (Carcharhiniformes: Scyliorhinidae) from north-east Australia.. 293 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 14684 records from Swiss National Orthoptera Databank. 2 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 64 records from Planktic foraminifera counts at CTD station PS55/083-1. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 70455 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 6 records from Pristipomoides amoenus (Snyder 1911), a valid species of jobfish (Pisces, Lutjanidae), with comparisons to P. argyrogrammicus (Valenciennes 1832). 36164 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 22 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 36 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 5 records from A new species of snook, Centropomus (Teleostei: Centropomidae), from northern South America, with notes on the geographic distribution of other species of the genus. 3 records from Nationalpark Harz Schul-AG Braunlage. 21 records from Tyrannosaurus And Torosaurus, Maestrichtian Dinosaurs From Trans-Pecos, Texas. 600 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 6 records from Description of a new species of deep-water snake eel, Ophichthus mccoskeri (Ophichthidae: Ophichthinae) from Andaman Sea, India. 2 records from New records of brittle stars (Echinodermata: Ophiuroidea) from the Lakshadweep atolls, northern Indian Ocean, with notes on Indophioderma ganapatii Sastry Marimuthu & Rajan, 2019. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 55 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 2 records from Nannofossil abundance of Hole 4-26A. 92 records from Planktic foraminifera abundance of Hole 22-212. 5 records from A new species of Pyrrhosphodrus (Hemiptera: Heteroptera: Reduviidae) from the Caatinga ecosystem in Brazil, with notes on the genus. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 12 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 9997 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 108 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatus, two new cichlid species (Teleostei, Perciformes) from Guinea, West Africa.. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 6 records from Abundance of benthos infauna at station GIK23065-1. 29137 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 41 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 283 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 27 records from Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species. 11 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 5462 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 14 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 228 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 16 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 47 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 139896 records from BioFokus. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 41 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 3199 records from Planktic foraminifera abundance of Hole 23-219. 71494 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1824 records from CNAN/Scorpiones. 104 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 94 records from Total foraminifera counts of multinet M26/1_MSN845. 8649 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 39 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 7 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 14 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 8 records from A new species of Orthosiphon (Lamiaceae) from Angola. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 281 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 5 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 439 records from Percentages of planktonic foraminifera species in sediment core V15-168. 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from
Keywords: GBIF; biodiversity; species occurrences